Olive polyphenols and bioavailable glutathione: Promising results in patients diagnosed with mild Alzheimer's disease - Massimo Marianetti; Silvia Pinna; Angelo Venuti; Gianfranco Liguri (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Recent studies highlighted the role of olive polyphenols in disrupting the ordered structure of highly cytotoxic amyloid beta protofibrils and the efficacy of a derivatized form of glutathione to counteract neuronal oxidative stress affecting specific brain regions at early stages of Alzheimer's disease (AD) pathogenesis. We performed a randomized cross‐over clinical trial to evaluate their potential benefits in mild AD. Methods Oleuropein and S‐acetyl glutathione were administered as dietary supplement for 6 months to 18 patients diagnosed for probable mild AD according to International Working Group 2 criteria. Patients underwent an extensive cognitive and behavioral neuropsychological test battery at the beginning and end of the study to evaluate cognitive deterioration, memory, visuospatial abilities, attention, language, executive functions, and behavioral disorders. We compared patients receiving treatment to patients receiving no treatment. Results All the measured neurocognitive parameters stabilized or improved after the treatment in all patients. Discussion Dietary supplement with olive polyphenols and bioavailable glutathione could be useful for patients diagnosed with mild AD.